Self-esteem and its associated factors among secondary school students in Klang District, Selangor. - Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Loh, J. W.; Chan, C. L.; Teh, P. C.; Tan, P. O. (2008)

(untitled)
Self-esteem is an important determinant of psychological well-being that is particularly problematic during adolescent life stage. There is a correlation between low self-esteem and other social problems among today's adolescents. This study was conducted to determine the mean self-esteem score, and to determine the association between self-esteem and age, sex, race, religion, number of siblings, ranking among siblings, family function, parental marital status and smoking among adolescents aged 12 to 20-years-old. A cross sectional study design using random cluster sampling method was done. Four out of a total of 35 secondary schools in Klang District, Selangor were selected. Respondents consisted of individual students in selected classes from the four selected schools. Data was collected using a self-administered, structured, pre-tested questionnaire and was analyzed using the SPSS version 12.0. Out of 1089 respondents, 793 completed the questionnaire (response rate 73.82%). The overall mean self-esteem score was 27.65. The mean self-esteem score for males (27.99) was slightly higher than females (27.31). The differences in the mean scores by race were statistically significant. There was a statistically significant relationship between mean self-esteem scores and sex, age, race, religion, number of siblings, smoking and family function. There was no statistically significant difference between mean self-esteem score with parental marital status and with ranking among siblings. The overall mean self-esteem score was 27.65. Self-esteem was associated with sex, age, race, religion, number of siblings, smoking and family function.